DEVELOPMENT OF A MODEL FOR PREVENTION AND SURVEILLANCE OF PREMATURE BIRTH BY PARTICIPATION OF THE DISTRICT HEALTH SERVICE NETWORK NUEA KHLONG DISTRICT KRABI PROVINCE - เทวินทรภักติ ลลิตา (Primary Health Care Journal (Northeastern Edition), 2024)
This study aimed to develop a model for preventing and monitoring preterm births through community network participation in Nuea Khlong District, Krabi Province, using the PDCA cycle combined with participatory work processes. The purposive sample included the operational network driving the development of a preterm birth prevention and monitoring model at Nuea Khlong Hospital and 14 sub-district health-promoting hospitals. The study was conducted over 6 months, from October 2023 to March 2024. Qualitative data were collected through interviews and analyzed using content analysis, while quantitative data were analyzed using descriptive statistics such as frequency and percentage. The results showed that current practices for preventing preterm births mainly involve screening for risk factors, but the existing guidelines lack specificity and do not comprehensively cover all associated risks. Education provided to at-risk pregnant women is also insufficient to raise awareness or enable effective self-care. To improve the model for preterm birth prevention and monitoring, two main components were identified: Antenatal Clinics in Sub-district Health Promoting Hospitals: Enhance the screening process to cover five key risk factors comprehensively. This requires improving guidelines to ensure all potential risks are addressed. Delivery Room at Nuea Khlong Hospital: Implement a consistent risk assessment for pregnant women experiencing preterm labor, using the same tools and criteria as the antenatal clinics. This uniform approach ensures comprehensive risk evaluations and appropriate care. Providing tailored education about preterm labor and management strategies based on individual risk factors is essential. These measures can effectively enhance preterm birth prevention and monitoring efforts in the region through active community participation.